Comparison of routine blood parameters by altitude and residence duration in the Western Sichuan Plateau - Liang Wan; Qing Yuan; Mingxia Tang; Zhu Zhu; Yanwu Liu; Zhenglin Huang; Shuzhi Zhou; Ling Zhang; Qiaoling Wang; Yuntao Guo; Jian Yang (Practical Laboratory Medicine)
Background: This study explores how routine blood test parameters change over time in acclimatized individuals at different altitudes on the Western Sichuan Plateau. Methods: Healthy men aged 20–40 from low-altitude areas who moved to Ganzi Prefecture to live and work were recruited. The observation sites were Guzan Town (1400 m), Kangding County Seat (2500 m), Luhuo County Seat (3400 m), and Litang County Seat (4100 m). Participants at the same altitude were grouped according to residence duration. The relationships between blood test parameters, altitude, and residence duration were analyzed. Results: After moving to the plateau, white blood cell, red blood cell, hemoglobin, and hematocrit levels rose quickly in the short term, then declined and stabilized. In contrast, platelet levels increased steadily and were positively correlated with altitude. Conclusions: Changes in blood parameters during high-altitude acclimatization are significant physiological responses to hypoxia and are affected by both altitude and residence duration.